Uma abordagem para apoio à aplicação de estudos experimentais em processo de negócio - Gonçalves, Tiago Lopes (2009)
With the advances of the Internet and the ability to offer the most powerful and effcient, it is possible that organizations, even though they are physically distributed, cooperate to provide and consume services of other organizations dynamically. To ensure the quality of the services involved in inter-organizational process, electronic contracts are established. An electronic contract is a document composed of information that govern a business process between organizations. As mechanisms and theories, business processes need to be highlighted and improved. Experiments in software engineering seek characterize, demonstrate, assess, predict, monitor and improve theories, processes, products and development tools software. This dissertation presents an approach to give support to the application of experimental studies in business processes. This approach is composed of procedures and guidelines for application of experiments and also a meta-model of artifacts to support the implementation of experiments that can store experimental studies, data and documents related. For the development of the proposal design, was used as objects of study the approach based on feature for the establishment of electronic contracts for Web services. Two experiments were performed and served as a means to ilustrate the elements of the proposed approach. An experiment with participants from academic on the scope of studies in vitro, and another experiment by an opinion search with participants who work in companies of software development and implementation services in Maringá and Dois Vizinhos. After data collection, the analysis was performed to identify the inuence of experience or inexperience of the participants in the use of the approach used as the object of study. The contributions of this work are: (i) the evaluation of the feature-based approach to the establishment of electronic contracts for Web services, (ii) to design an approach to support the application of experimental studies in business process with procedures and guidelines for implementation of experiments, (iii) a meta-model of artifacts to support the implementation of experiments that will contribute to a number of artifacts stored properly and described to facilitate future experiments and (iii) the establishment of a view for the planning and execution of experiments in business process.